Feasibility and acceptability of a rural, pragmatic, telemedicine‐delivered healthy lifestyle programme - John A. Batsis; Auden C. McClure; Aaron B. Weintraub; David F. Kotz; Sivan Rotenberg; Summer B. Cook; Diane Gilbert‐Diamond; Kevin Curtis; Courtney J. Stevens; Diane Sette; Richard I. Rothstein (Wiley, 2019)
Summary Background The public health crisis of obesity leads to increasing morbidity that are even more profound in certain populations such as rural adults. Live, two‐way video‐conferencing is a modality that can potentially surmount geographic barriers and staffing shortages. Methods Patients from the Dartmouth‐Hitchcock Weight and Wellness Center were recruited into a pragmatic, single‐arm, nonrandomized study of a remotely delivered 16‐week evidence‐based healthy lifestyle programme. Patients were provided hardware and appropriate software allowing for remote participation in all sessions, outside of the clinic setting. Our primary outcomes were feasibility and acceptability of the telemedicine intervention, as well as potential effectiveness on anthropometric and functional measures. Results Of 62 participants approached, we enrolled 37, of which 27 completed at least 75% of the 16‐week programme sessions (27% attrition). Mean age was 46.9 ± 11.6 years (88.9% female), with a mean body mass index of 41.3 ± 7.1 kg/m2 and mean waist circumference of 120.7 ± 16.8 cm. Mean patient participant satisfaction regarding the telemedicine approach was favourable (4.48 ± 0.58 on 1‐5 Likert scale-low to high) and 67.6/75 on standardized questionnaire. Mean weight loss at 16 weeks was 2.22 ± 3.18 kg representing a 2.1% change (P < .001), with a loss in waist circumference of 3.4% (P = .001). Fat mass and visceral fat were significantly lower at 16 weeks (2.9% and 12.5%; both P < .05), with marginal improvement in appendicular skeletal muscle mass (1.7%). In the 30‐second sit‐to‐stand test, a mean improvement of 2.46 stands (P = .005) was observed. Conclusion A telemedicine‐delivered, intensive weight loss intervention is feasible, acceptable, and potentially effective in rural adults seeking weight loss.